Digitalisasi Jaminan Fidusia: Analisis Efisiensi dan Keamanan dalam Pendaftaran Online - Lorensia Ayu Kusuma Dewi (Universitas Wahid Hasyim, 2025)
The digitalization of fiduciary guarantees through online registration aims to increase efficiency and transparency in accordance with Law No. 42 of 1999 concerning Fiduciary Guarantees. The purpose of this study is to analyze the digitalization of online-based fiduciary guarantees, with a focus on the efficiency and security of the digital fiduciary system. This study examines security threats and their mitigation strategies, including the risk of data leaks, cyber attacks, and forgery of electronic documents that can threaten the validity of fiduciary guarantees. To overcome these challenges, mitigation measures are needed such as data encryption, use of blockchain, increased regulation, and strengthening cybersecurity infrastructure. With the normative legal analysis method, this study aims to maximize efficiency without sacrificing legal protection and security. The results of the study show that the application of the right technology can speed up the process and increase the transparency of fiduciary transparency, while minimizing security risks.